Boundaries of the Episteme: Decolonising the International Law Curriculum. (2nd September 2018) - Nienaber, Annelize
ABSTRACT: Debates on many university campuses call for a refocused or "decolonised" university curriculum. These demands reject curricula that are considered narrow and unreformed and cultures that position many in the university as unwelcome outsiders. In response to these calls, there have been attempts at a renewal of the South African higher education system, and several universities are currently revising their curricula in an endeavour to be responsive to students' concerns. Drawing on Michel Foucault's idea of the "episteme", this article narrates a university professor's quest to reconceptualise the undergraduate and postgraduate international law curricula at the university where she lectures, and highlights the lessons she has learnt in the process about the boundaries of her and other international law scholars' knowledge and ways of knowing.